Digital version of the Rapid Automatized Naming (RAN): a contribution to early detection of reading problems in children - Davino Silva Junior; Luciana Cidrim; Antonio Roazzi; Francisco Madeiro (Revista CEFAC, 2019)
ABSTRACT Purpose: to present a digital version of the Rapid Automatized Naming (RAN) test, designed to be used as an auxiliary tool for early detection of reading problems in children. Methods: the application was designed to provide resources, such as: a) registration; b) information security with the online authentication system - individuals are only seen by the person who registered them and, c) history of the results. In order to know the impressions of speech therapists and professionals of children’s education area about this digital version of RAN test, a public opinion survey was conducted with unidentified participants by Google Forms. Results: the application has an automatic speech recognition and allows registering and accessing the history of the application, including statistical evaluation of the results. The application features a responsive interface that adapts to the dimensions of the mobile device with soft colors, and offers a variety of text font options. The images of the objects of the digital version were elaborated by a designer. Conclusion: the application presents itself as a useful digital tool that assists professionals to evaluate, early, children with reading difficulties, highlighting the following elements: exclusive and appropriate images to children’s universe and the function of storing the results of users tested.